Macromol. Mater. Eng. 12/2017. Issue 12 (13th December 2017) - Brüster, Berit; Amozoqueño, Camilo; Grysan, Patrick; Peral, Inma; Watts, Benjamin; Raquez, Jean‐Marie; Dubois, Philippe; Addiego, Frédéric
Abstract : Front Cover : The reactive plasticization of polylactide with acrylated poly(ethylene glycol) (acrylPEG) forms grafted inclusions inside the matrix. The inclusions exhibit a core‐shell structure, where the core consisted of less dense poly(acrylPEG) than the shell. Upon drawing, the inclusions are stretched, and submicron cracks form between inclusions. This is reported by Berit Brüster, Camilo Amozoqueño, Patrick Grysan, Inma Peral, Benjamin Watts, Jean‐Marie Raquez, Philippe Dubois, and Frédéric Addiego, article number1700326 .